SAT0119 Effect of Abatacept on Bone Homeostasis and Osteopontin in Rheumatoid Arthritis. (23rd January 2014) - Kitano, M.; Kitano, S.; Ishizu, M.; Furukawa, T.; Yoshikawa, T.; Fujita, K.; Katashima, Y.; Sato, C.; Saito, A.; Nishioka, A.; Sekiguchi, M.; Azuma, N.; et al.
Abstract : Background: Abatacept (CTLA4-Ig) is a new therapeutic agent used for rheumatoid arthritis (RA). Recently, it is reported that CTLA-4 directly inhibits osteoclast formation. On the other hand, Osteopontin (OPN) is produced by activated T lymphocytes and has been recognized as one of the key molecules for osteoclastic bone-resorption in RA. However, the effect of abatacept on bone homeostasis and OPN production in RA is poorly understood. In this study, we investigated the effects of abatacept on biochemical markers of bone, serum soluble receptor activator of NF-kappa B ligand (sRANKL), osteoprotegerin (OPG), and plasma osteopontin (OPN) in patients with RA. Objectives: To demonstrate the effect of abatacept on bone homeostasis in RA. Methods: 24 patients with RA (19 females, 5 males; age 59.8±14.7 years; disease duration 6.1±8.0 years; stage 2.0±1.2; class 1.8±0.6; DAS28-CRP 4.6±1.4; SDAI 26.7±12.8; use of MTX 83%; average dose of MTX 5.9±3.3mg/week; use of PSL 71%; average dose of PSL 3.9±3.2mg/day) were started on treatment with abatacept for 24 weeks. All patients were biologics naïve. In addition, circulating levels of type I collagen cross-linked N-telopeptides (NTx), osteocalcin, sRANKL, OPG, and plasma OPNwere examined by ELISA at baseline and after 12 and 24 weeks. Results: After 24 weeks of abatacepttreatment, DAS28-CRP and SDAI decreased significantly from the baseline (4.6±1.4 vs 2.5±0.9; p<0.01, 26.7±12.8 vs 8.6±6.0; p<0.01, respectively), so that 14 patients achieved DAS28-CRP remission. After 12 weeks, average of NTx levels decreased significantly from the baseline (16.27±5.81 vs 14.23±3.48 nmol BCE/l; p<0.01). After 24 weeks, average of osteocalcin levels increased significantly (5.80±3.02vs 6.45±2.61 ng/ml; p<0.05) and average of OPN levels decreased significantly from the baseline (101.57±57.40 vs 71.76±29.49 pg/ml; p<0.01). Average of RANKL levels tended to decrease from the baseline ((0.22±0.39 vs 0.12±0.20 pmol/l; p=0.06), whereas average of OPG levels did not change significantly from the baseline (4.67±1.96 vs 4.90±2.44 pmol/L; p=0.17). Conclusions: These findings suggest that abatacept improves systemic bone metabolism in patient with RA through the increase of bone formation markers and the decrease of bone degradation markers. We consider that these mechanism result from the regulation of OPN and RANKL expression in activated T lymphocytes. Consequently, abatacept may control osteoclastic-bone destruction in RA via the suppression of RANKL induced-osteoclastogenesis and OPN induced-osteoclast attachment of bone surface. Disclosure of Interest: None Declared